AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL 96% DAUN BANGKAL (Nauclea subdita) TERHADAP BAKTERI Staphylococcus aureus - Monica, Cahya; Zamzani, Irfan; Siti Nashihah (Jurnal Insan Farmasi Indonesia, 2024)
Bangkal (Nauclea subdita) is a typical plant in the southern part of the island of Borneo. In everyday life, bangkal leaves are used to treat wounds, ulcers, toothache, fever and diarrhea. The purpose of this study was to measure and determine the antibacterial activity of the ethanol extract of bangkal leaves against Staphylococcus aureus using the Ultrasonic Assisted Extraction (UAE) method. Bangkal leaves were extracted by UAE using 96% ethanol. The antibacterial inhibition test was carried out using the Kirby-Bauer disc diffusion method. Testing of antibacterial inhibition zones of Bangkal leaf extract against Staphylococcus aureus bacteria had an effect or significantly different with concentrations of 40%, 60%, 80%, 100% respectively and produced antibacterial activity with inhibition zones of 12.7±0.06 respectively. mm, 13.9±0.00 mm, 15±0.00 mm, 16±0.00mm. The results of the antibacterial activity examination showed that the ethanolic extract of bangkal leaves could inhibit the growth of Staphylococcus aureus at a concentration of 40% with an inhibition zone diameter of 12.7 mm and the highest concentration at 100% with an inhibition zone diameter of 16.00 mm. This indicates that the extract of bangkal leaves has antibacterial activity against Staphylococcus aureus which has an inhibition zone with a moderate to strong category.